Gambaran Pola Makan Ibu Hamil Kekurangan Energi Kronis Wilayah Kerja Puskesmas Cilacap Selatan II Kabupaten Cilacap - Endah Purwatiningsih; Dewi Ambarwati (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Chronic Energy Deficiency (SEZ) in pregnant women is still a significant nutritional problem in Indonesia, contributing to maternal and infant morbidity such as the risk of Low Birth Weight (BBLR). The prevalence of SEZs in Central Java increased from 158,327 cases in 2022 to 344,806 in 2023. At the South Cilacap II Health Center, there were 24 cases of pregnant women in the SEZ out of 175 pregnant women in December 2024. An inadequate diet is often the main cause of SEZs. This study aims to describe the diet of pregnant women with SEZs in the working area of the South Cilacap II Health Center. This study used a quantitative descriptive method by involving as many as 85 pregnant women as respondents, consisting of 26 pregnant women in KEK and 59 pregnant women in non-KEK (as a comparison group). The sampling technique used incidental sampling. Data was collected using the Food Frequency Questionnaire (FFQ), then analyzed descriptively through frequency and percentage distribution. Food intake is the main indicator in the assessment of diet. The majority of pregnant women in KEK (88.5%; 23 out of 26 KEK respondents) have a diet that is categorized as "lacking". On the other hand, in the non-KEK pregnant women, the majority (83.1%; 49 out of 59 respondents) showed a "good" diet. Insufficient nutrition has been shown to be closely correlated with the incidence of SEZs. Maternal health during pregnancy is greatly influenced by the quality and quantity of daily food intake. Balanced nutrition must be met to support fetal growth and maternal health. Nutrition counseling and routine education from health workers are highly recommended. It is suggested that the South Cilacap II Health Center increase health promotion efforts through pregnant women's classes, individual counseling, and the provision of educational materials on a balanced nutritious diet to prevent and overcome KEK in pregnant women.